Motivasi Kerja Islam dan Etos Kerja Islam Karyawan Bank Jatim Syariah Cabang Surabaya - Bhirawa Anoraga; Ari Prasetyo (Universitas Airlangga, 2015)
This research was aimed to investigate the effect of Islamic work motivation to the employee Islamic work ethics on Jatim Sharia Bank Branch Surabaya. This study used questionnaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is the employee Islamic work ethics and the independent variable (X) is Islamic work motivation. The research sample were taken by census. The research sample was 54 employees working in Jatim Sharia Bank Branch Surabaya.Based on the findings, it obtained simple linear regression equation : Y = 2,739 + 0,353X. The magnitude of the influence of Islamic work ethics to the employees Islamic work ethics on Jatim Sharia Branch Surabaya is the R2 value of 0,446 (44,6%). The result show that employee Islamic work ethics on Jatim Sharia Bank Branch Surabaya significantly affect by Islamic work motivation.